2022
DOI: 10.1136/sextrans-2022-055516
|View full text |Cite
|
Sign up to set email alerts
|

How did the COVID-19 pandemic affect access to condoms, chlamydia and HIV testing, and cervical cancer screening at a population level in Britain? (Natsal-COVID)

Abstract: ObjectivesTo investigate how differential access to key interventions to reduce STIs, HIV and their sequelae changed during the COVID-19 pandemic.MethodsBritish participants (18–59 years) completed a cross-sectional web survey 1 year (March–April 2021) after the initial lockdown in Britain. Quota-based sampling and weighting resulted in a quasi-representative population sample. We compared Natsal-COVID data with Natsal-3, a household-based probability sample cross-sectional survey (16–74 years) conducted in 20… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…The Natsal-COVID study used a quasi-representative sample of the UK population and estimated that 36.8% (95% confidence interval (CI): 27.8%–46.8%) of GBMSM had had difficulty accessing condoms because of the pandemic, five times higher than our figure of 7.3% among GBMSM. 8 However, the Natsal-COVID sample included a smaller number of GBMSM ( n = 183), reflecting how it was a study of the general population, and defined GBMSM differently (any same-sex experience in the past 5 years). Indeed, it is worth noting that Natsal-COVID’s estimate was considerably lower at 4.9% (95% CI: 2.1%–11.1%) among the 117 participants who identified as gay, which is more in line with our study’s estimate.…”
Section: Comparison With Other Literaturementioning
confidence: 99%
See 3 more Smart Citations
“…The Natsal-COVID study used a quasi-representative sample of the UK population and estimated that 36.8% (95% confidence interval (CI): 27.8%–46.8%) of GBMSM had had difficulty accessing condoms because of the pandemic, five times higher than our figure of 7.3% among GBMSM. 8 However, the Natsal-COVID sample included a smaller number of GBMSM ( n = 183), reflecting how it was a study of the general population, and defined GBMSM differently (any same-sex experience in the past 5 years). Indeed, it is worth noting that Natsal-COVID’s estimate was considerably lower at 4.9% (95% CI: 2.1%–11.1%) among the 117 participants who identified as gay, which is more in line with our study’s estimate.…”
Section: Comparison With Other Literaturementioning
confidence: 99%
“…It is interesting to note that this general population study found, as we did, that younger GBMSM (aged 18–29 years) were more likely to report difficulty accessing condoms because of the pandemic (50.4%). 8 This age effect suggests a continuation of inequalities that preceded the COVID-19 pandemic, 9 perhaps reflecting how knowledge of, and resources to access condoms, increases with age. However, we are unsure as to the cumulative effect of the pandemic on the magnitude of associations with age and difficulties accessing condoms.…”
Section: Comparison With Other Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…But Dema et al found that the pandemic had resulted in a 50% unmet need for condoms among MSM aged 18 to 29 years. Because condoms provided by health services are further reduced, and finding condoms was more challenging [11].…”
Section: Changes Of Sexual Behavior and Condemn Usagementioning
confidence: 99%